Research of Geostress Test in Underground Powerhouse Area of a Pumped Storage Power Station - GENG Bijun; REN Xin; ZHANG Xiangfu; YUAN Tao; ZHONG Juguang (Renmin Zhujiang)
The geotress is an important basis for the stability evaluation of the surrounding rock in the underground powerhouse area of a pumped storage power station.This paper conducts a geostress test in the underground powerhouse area and high-pressure bifurcated pipe of a proposed pumped storage power station by means of hydraulic fracturing to obtain the plane stress test parameters such as fracture pressure,instantaneous closing pressure and reopening pressure of surrounding rock,and calculates the three-dimensional geostress of the surrounding rock based on these parameters. Results show that:For the three testing sections,the maximum principal stress is less than 10 MPa,the dip angle is between 56.64° and 68.50°,and the azimuth angle is between 340.34° and 18.61°;The intermediate principal stress and the minimum principal stress are between 5.41~7.61 MPa and 4.08~6.71 MPa,respectively,with small dip angle;The vertical stress component is basically consistent with the theoretical calculation of gravity stress,which indicates that the stress field of underground powerhouse and high-pressure bifurcated pipe area is mainly gravity stress field.The results of geostress test by hydraulic fracturing has good regularity,which can serve as reference for similar projects.